國小六年級學生犯罪軟體防治之教材發展與評鑑：以恐懼訴求為教學設計原則之研究 The Use of Fear Appeals in the Development and Evaluation of an Anti-Crimeware Courseware for Taiwanese Sixth Graders - 鄧達鈞 Ta-Chun Teng (Journal of Research in Education Sciences, 2012)
本研究之目的為發展國小六年級學童犯罪軟體防治教材，並探討其學習成效。本教材以系統化教學設計進行，並以傳播學領域之「恐懼訴求」為教學設計方式。在實驗設計中分別以不同高低之感受性及嚴重性設計四類不同訴求教材，作為教學實驗之自變項，以探究130位六年級學生之犯罪軟體防治態度、認知概念、問題解決及課後繼續行為之學習成效。研究結果指出：整體而言，接受高感受及高嚴重教材之學生的學習成效優於其他組別。本研究結果可提供未來相關研究、教學設計之參考。 This study describes the development of an anti-crimeware courseware for schoolchildren in Taiwan and examines its pedagogical effectiveness. The instructional design adopted the ADDIE model and integrated the fear appeals approach. A 2-by-2 factorial experimental design was used to test the four possible combinations of two levels (high and low) and two factors (perceived susceptibility and severity) of fear appeals. The participants in this study included 130 sixth graders. Using immediate and delayed individual tests, this study examined their anti-crimeware attitudes, cognitive concepts, and problem solving skills. The results indicated that the High-Susceptibility/High-Severity (H-Su/H-Se) group outperformed the other three groups. Further explanations and interpretations of the results are provided, and suggestions for future research are proposed.